2021
DOI: 10.1016/j.omtn.2021.02.024
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNAs LINC00261 and LINC00665 are upregulated in long-term prostate cancer adaptation after radiotherapy

Abstract: Long non-coding RNAs (lncRNAs) have been shown to impact important biological functions such as proliferation, survival, and genomic stability. To analyze radiation-induced lncRNA expression in human tumors, we irradiated prostate cancer cells with a single dose of 10 Gy or a multifractionated radiotherapeutic regimen of 10 fractions with a dose of 1 Gy (10 × 1 Gy) during 5 days. We found a stable upregulation of the lncRNA LINC00261 and LINC00665 at 2 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Irradiation was performed at room temperature using single doses or multiple fractions of 320 kV X-rays with a dose-rate of 2.3 Gy/min (Precision X-Ray Inc.). Multifractionated radiation was carried out as described before with two times 1 Gy per day (with a 6 h time interval between both radiations) 34 . At 24 h after the final radiation dose or 6 d after the first radiation dose (Supplementary Figure S1), total RNA was extracted for short-term (ST) gene analysis (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Irradiation was performed at room temperature using single doses or multiple fractions of 320 kV X-rays with a dose-rate of 2.3 Gy/min (Precision X-Ray Inc.). Multifractionated radiation was carried out as described before with two times 1 Gy per day (with a 6 h time interval between both radiations) 34 . At 24 h after the final radiation dose or 6 d after the first radiation dose (Supplementary Figure S1), total RNA was extracted for short-term (ST) gene analysis (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from three replicates using a QIA shredder spin column (Catalog no. 79654, Qiagen) as published previously 34 . The RNeasy mini kit (Qiagen) was used to purify the extracted RNA.…”
Section: Methodsmentioning
confidence: 99%
“…These results revealed that LINC00665 could inhibit the expression of KLF2 by interacting with EZH2 and LSD1 to promote prostate cancer progression ( Xue et al, 2021 ). In particular, one study showed that LINC0065 was steadily upregulated in prostate cancer cells 2 months after radiotherapy ( Eke et al, 2021 ). This study proved that LINC00665 regulated RBBP8, XPC, and BRCA1 gene expression ( Eke et al, 2021 ).…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%
“… 6 One such LINC, namely LINC00261, is known to be insufficiently expressed in a wide variety of cancers, ranging from pancreatic cancer, colon cancer, to prostate cancer, while newer studies have also implicated LINC00261 with cancer cell viability, mobility radioresistance, and poor prognosis. 7–9 Regarding EC, LINC00261 can promotes EC cell sensitivity to drugs, whereas, silencing of LINC00261 was previously shown to augment EC growth and diminish apoptosis and sensitivity. 10 Mechanistic-based studies have also indicated that LINC00261 can mediate tumorigenesis and cancer progression by means of competing endogenous RNA (ceRNA) interactions.…”
Section: Introductionmentioning
confidence: 99%